Effect of aspirin on acute changes in peripheral arterial stiffness and endothelial function following exertional heat stress in firefighters: The factorial group results of the Enhanced Firefighter Rehab Trial. (June 2015) - Olafiranye, Oladipupo; Hostler, David; Winger, Daniel G; Wang, Li; Reis, Steven E
Peripheral arterial stiffness and endothelial function, which are independent predictors of cardiac events, are abnormal in firefighters. We examined the effects of aspirin on peripheral arterial stiffness and endothelial function in firefighters. Fifty-two firefighters were randomized to receive daily 81 mg aspirin or placebo for 14 days before treadmill exercise in thermal protection clothing, and a single dose of 325 mg aspirin or placebo immediately following exertion. Peripheral arterial augmentation index adjusted for a heart rate of 75 (AI75) and reactive hyperemia index (RHI) were determined immediately before, and 30, 60, and 90 minutes after exertion. Low-dose aspirin was associated with lower AI75 (–15.25±9.25 vs −8.08±10.70, p =0.014) but not RHI. On repeated measures analysis, treatment with low-dose aspirin before, but not single-dose aspirin after exertion, was associated with lower AI75 following exertional heat stress ( p =0.018). Low-dose aspirin improved peripheral arterial stiffness and wave reflection but not endothelial function in firefighters.